A Non-Monotonic Description Logics Model for Merging Terminologies - Moguillansky, Martin Oscar (2007)
In order to deal with the Ontology Change problem and considering an environment where Description Logics (DLs) are used to describe ontologies, the question of how to integrate distributed ontologies appears to be in touch with Belief Revision since DL terminologies may define same concept descriptions of a not necessarily same world model. A possible alternative to reason about these concepts is to generate unique concept descriptions in a different terminology. This new terminology needs to be consistently created, trying to deal with the minimal change problem, and moreover, yielding a non-monotonic layer to express ontological knowledge in order to be further updated with new distributed ontologies.